Istihsan and Istishab in Islamic Legal Reasoning: Towards the Extension of Legal Finding in the Context of Indonesia - Muslimin, JM; Kharis, M Abdul (Al-Risalah, 2020)
This article explores the debate among Muslim jurists on istiá¸¥sÄn and istiá¹£hÄb and the ability of both to solve Islamic legal cases in Indonesia. The research is done through normative legal approach by referring to various literatures in the elaboration of legal concepts. The concepts of law (istiá¸¥sÄn and istiá¹£hÄb) are discussed and become the central topic. At the end, those concepts are applied in the cases to draw normative conclusions. The result of this research shows that though istiá¸¥sÄn and istiá¹£hÄb are still debatable, both of the two have a strong influence and relevance to be applied. In the Indonesian context, istiá¸¥sÄn and istiá¹£hÄb reasoning, may be combined or separated, can be used to promulgate the obligatory registration of marriage, the application of health protocol of Covid-19 during prayer in the mosque in the time of pandemic, and possibility of using credit card and e-commerce for transaction, the acceptance of Pancasila as the basis of the Republic of Indonesia, the legitimacy of 1945 constitution, democracy, and current principles of modern jurisprudence (such as the principles of pre-assumption of innocent). That is due to the fact of their virtues for public life (maá¹£laá¸¥ah muá¸¥aqqaqah), and no exact prohibition is found in al-QurÊ¼an and Hadith (ibÄá¸¥ah aá¹£liyyah). In short, by using istiá¸¥sÄn and istiá¹£hÄb, such mentioned recent cases may be solved and logics of legal reasoning can be extended.